Jeux de mots qui percutent, jeux de mots qui enquêtent: la rhétorique engagée d’Abdelhak Serhane - Todesco, Francesca (Ponti/Ponts, 2021)
The study takes into consideration some wordplays in the narrative and poetry of Moroccan writer A. Serhane, observing and deepening their rhetorical and argumentative significance. The many virtuosities of the work of this “bohémien de la parole [...] à la mémoire remplie d’échos”, concern sounds and letters or words and their lexical, syntactic or semantic elaborations, created by substitution or concatenation, on the syntagmatic or paradigmatic axis of the speech. They give rise to a critical metalanguage in which stylistic deviations amplify the force of the ideological commitment of the author and the depth of his inner reflection. The essay proves that Serhane plays with words to play with ideas , grasping the form and the sense of many linguistic manipulations, produced by ironic mentions, parodic echoes, metaplasms and sound creations of a polyphonic and plural fictional and poetic work. It’s surely worthy of note in the panorama of Maghreb post-modern literature.